Perancangan Ontologi untuk Sistem Rekomendasi Tempat Makan di Bali - Ni Putu Diva Damayanthi; Ida Ayu Gde Suwiprabayanti Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
As we know, Bali is one of the world destinations and can develop its tourism well. Apart from being famous for its natural beauty nature, culture and friendly people, Bali also offers a variety of culinary delights for tourists that can be ordered at restaurants, tourist objects or at hotels there. Many recommendations for places or restaurants/eating places with various mainstay menus are needed to make it easier for tourists to find the food menus they want and meet their budget. In this research expected to be solved by combining the Methodology technique with a semantic ontology model. Designing an ontology model for restaurant/dining recommendations in Bali using the protégé application, the ontology model was developed into a structure for students with classes, attributes, and other elements arranged hierarchically. To get the right answers, the ontology assessment procedure using SPARQL queries is employed.